Type 2 diabetes: basic clinical and laboratory parameters and risk of cardiovascular death - O D Rymar; L V Shcherbakova; A O Shchetinina; S V Mustafina; Y I Ragino; M Bobak; S K Malyutina (Российский кардиологический журнал, 2020)
Aim. To evaluate the basic clinical and laboratory parameters and their relationship with the 14-year risk of cardiovascular death in individuals with type 2 diabetes (T2D).Material and methods. A prospective case-control study of a sample of Novosibirsk residents with T2D was performed. An initial examination was conducted as part of the HAPIEE project in 2003-2005. The follow-up period lasted until 2017 and amounted to 13,7±0,7 years. The case group consisted of 145 people (mean age — 62,0±5,7 years) with recorded cardiovascular death. Control group — 272 people (mean age — 57,9±6,6 years) without recorded death as of December 31, 2017. Persons with a history of non-fatal myocardial infarction and/or stroke at the initial examination were excluded. Blood pressure (BP), biochemical, anthropometric and socio-demographic data were determined. Logistic regression models were used to analyze the association of clinical and laboratory parameters with the risk of cardiovascular death.Results. T2D subjects with recorded cardiovascular death at the initial examination had a longer duration of the disease, higher fasting plasma glucose (FPG) and anthropometric parameters (body mass index (BMI), waist circumference (WC) (in  women)), systolic blood pressure (SBP) and diastolic blood pressure (DBP). In individuals of both sexes, the risk of cardiovascular death increased 2,2 times with WC >95 cm, 2,3 times with an increased WC/HC ratio, 2,2 times with a BMI ≥30 kg/m2, 1,9 times with physical activity <3 hours/week, 2 times for smokers and those with a single marital status, 3,5 times for hypertensive people, 2 times with FPG ≥7,5 mmol/L and longer duration of diabetes.Conclusion. Fourteen-year follow-up revealed that individuals with T2D have associations of cardiovascular death with both conventional risk factors such as hypertension, abdominal obesity, low level of physical activity, smoking, single marital status, and diabetes-related ones — FPG and the duration of diabetes.